Dinamika Politik Identitas Dalam Sumber Ajaran Islam di Indonesia : Studi Kasus Pemilu - Miftahul Huda N M; Muh. Nur Rochim Maksum (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
: Identity politics is political strategy that uses social identities such as ethnicity, religion, and gender to gain electoral support. This article explains how the phenomenon and influence of identity politics in Indonesia, the issue of identity politics in the 2024 elections and identity politics based on Islamic teaching sources. Identity politics can be positive or negative. Positive in nature means that it makes an impetus to recognize and accommodate the existence of comparisons, even to the extent of recognizing the predicate or privilege of a region or nation due to a basis that can be understood historically and logically. It is negative when there is a difference between one group and another, for example the domination between the majority and the minority. Identity politics grows over a social group that considers intimidated and discriminated against by government and state power in regulating government order, this condition which then becomes the basis for the birth of identity politics in state issues.